Safety and efficacy of a nonmyeloablative pretransplant conditioning regimen using total lymphoid irradiation with volumetric modulated arc therapy in healthy dogs: A pilot study. Issue 4 (13th March 2021) - Kim, Sangho; Hosoya, Kenji; Fukayama, Natsuki; Deguchi, Tatsuya; Okumura, Masahiro
Abstract: Allogeneic hematopoietic cell transplantation (HCT) has been an effective treatment for human patients with haematological malignancies (Baron & Storb, 2006; Bair et al., 2020; Copelan et al., 2019). However, the optimal pretransplant conditioning treatment is unclear in canine allogeneic HCT. This pilot study aimed to evaluate the safety and efficacy of total lymphoid irradiation (TLI) with volumetric modulated arc therapy (VMAT) for a nonmyeloablative HCT conditioning. Six healthy dogs were treated with 8 or 12 Gy TLI using VMAT. Haematological and physical changes were recorded over 8 weeks. To assess the effect of peripheral lymphocyte condition, lymphocyte subset and proliferative ability were examined. At the end of the experiment, necropsy was performed. All dogs showed mild‐to‐moderate neutropenia and thrombocytopenia, and these haematological changes resolved spontaneously. One dog treated with 8 Gy TLI developed transient cutaneous infection. No major complication was seen in the other seven dogs. Myelocytes and erythroblast cytopenia of bone marrow were detected in two dogs treated with 12 Gy TLI. This study is the first report of TLI using VMAT in dogs, and results suggest that this regimen is a feasible nonmyeloablative treatment. Abstract : This study evaluated the safety and feasibility of total lymphoid irradiation using volumetric modulated arc therapy as pretransplant conditioning treatment in canine hematopoietic cell transplantation.